2020
DOI: 10.1016/j.nicl.2020.102398
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the structural and functional connectivity of the frontoparietal network underlies symptomatic anxiety in late-life depression

Abstract: Highlights LLD patients present lower functional connectivity in the right FPN. LLD patients present impaired white matter integrity in tracts to the right FPN. FPN alterations were negatively correlated with anxiety severity in LLD patients. The right IFG might be a crucial hub underlying the neuropathology of LLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…Furthermore, higher plasma homocysteine levels were associated with poorer cognition in patients with LLD ( Zhou et al, 2020 ). In the current study, we discovered lower FA values in the bilateral inferior longitudinal fasciculus in LLD patients, which is consistent with the majority of prior findings on FA values in patients with LLD ( Alves et al, 2012 ; Mettenburg et al, 2012 ; Guo et al, 2014 ; Li et al, 2014 , 2020 ; Wen et al, 2014 ; Emsell et al, 2017 ), confirming the LLD disconnection theory. Furthermore, we recognized a reverse relationship between plasma Hcy concentrations and FA values in the forceps minor in patients with LLD, suggesting that Hcy level is related to the WM structure.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, higher plasma homocysteine levels were associated with poorer cognition in patients with LLD ( Zhou et al, 2020 ). In the current study, we discovered lower FA values in the bilateral inferior longitudinal fasciculus in LLD patients, which is consistent with the majority of prior findings on FA values in patients with LLD ( Alves et al, 2012 ; Mettenburg et al, 2012 ; Guo et al, 2014 ; Li et al, 2014 , 2020 ; Wen et al, 2014 ; Emsell et al, 2017 ), confirming the LLD disconnection theory. Furthermore, we recognized a reverse relationship between plasma Hcy concentrations and FA values in the forceps minor in patients with LLD, suggesting that Hcy level is related to the WM structure.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, altered intrinsic connectivity between or within networks was observed in resting state. The RSFC within the FPN was inversely correlated with the severity of anxiety in line with the resting-state studies that indicate that the RSFC of the FPN was negatively correlated with the anxiety level ( 73 , 74 ), indicating that dysfunction in the FPN may be associated with anxiety in informal PD caregivers. Furthermore, the RSFC between the DMN and the FPN and within FPN was positively correlated with cognitive function, including execution, attention/working memory, memory, and visuospatial function.…”
Section: Discussionsupporting
confidence: 86%
“…Illness duration also correlated with a volume reduction of the hippocampus, putamen, insula, and mPFC ( 20 22 ). Resting-state functional magnetic resonance imaging (fMRI) studies reported a reduction of connectivity between the amygdala and dorsal frontal regions in LLD patients ( 23 ), with disruptions of the fronto-parietal network ( 24 ). Brain connectivity between the fronto-parietal network and regions that are involved in sensory information processing were restored after MBCT in patients with major depression ( 25 ).…”
Section: Introductionmentioning
confidence: 99%